2018
DOI: 10.1007/s10943-018-0659-2
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and Subjective Well-Being of the Central and Eastern European’s Elderly Population

Abstract: The paper examines the relation between religiosity and cognitive appraisal of the subjective well-being of the Central and Eastern European's elderly population. The first part of the paper is dedicated to examining of the scientific literature. In the second part, the authors explore the data basis corresponding to the 6th wave of World Value Survey. The authors use the heterogeneous correlation and the multi-linear regression analysis in order to explain the relation between religiosity and subjective well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…At the same time, for both women and men religiosity and nancial status controlled by sociodemographic variables were bene cial for their happiness. The same as in the elderly from East and Central European countries including Poland nancial status positively predicted happiness both in men and in women (Bodogai et al, 2020). The prediction strength among men was almost the same value as in the above-cited study, but in the group of women, it was smaller, but the identi ed gender difference was not statistically signi cant in the moderation test.…”
Section: Discussionsupporting
confidence: 59%
“…At the same time, for both women and men religiosity and nancial status controlled by sociodemographic variables were bene cial for their happiness. The same as in the elderly from East and Central European countries including Poland nancial status positively predicted happiness both in men and in women (Bodogai et al, 2020). The prediction strength among men was almost the same value as in the above-cited study, but in the group of women, it was smaller, but the identi ed gender difference was not statistically signi cant in the moderation test.…”
Section: Discussionsupporting
confidence: 59%
“…Nevertheless, also other European countries such as Poland or Slovenia have high prevalence of the Roman Catholic religion. Furthermore, previous research also showed correlation between the Roman-Catholic religious affiliation and life satisfaction in eastern and central European countries (Bodogai et al, 2020). As the study sample consisted predominantly of female participants, our results may be less generalizable to male population.…”
Section: Discussionmentioning
confidence: 73%
“…The religiosity may enhance subjective wellbeing, thus lowering the impact of MDD [33]. Villani et al [34] found that religious identity commitment positively predicted satisfaction with life among religious, but not among uncertain individuals.…”
Section: Introductionmentioning
confidence: 99%